Impact of wall materials on the physicochemical properties of spray-dried microencapsulated soybean oil bodies - Grace Asantewaa Twumasi; Wipavadee Sangadkit; Nitjaree Manareet; Aunchalee Aussanasuwannakul; Toya Ishii; Jiraporn Sirison (Food Hydrocolloids for Health)
Soybean oil bodies (SOB) are naturally occurring emulsions with promising applications in food formulations. However, their sensitivity to environmental factors such as moisture, oxidation, and temperature fluctuations, coupled with their native instability, makes them difficult to incorporate into food products. This necessitates effective encapsulation strategies to preserve their bioactive properties, extend shelf life, and improve processability. This study aimed to encapsulate SOB using a spray drying technique with maltodextrin, whey protein isolate, and soy lecithin as wall materials. The encapsulation efficiency (56.43 - 85.41%) demonstrated the effective retention of oil bodies within the microparticles. The resulting powders were further characterized for powder yield, moisture content, water activity, color, wettability, solubility, hygroscopicity, particle size, surface charge, and morphological properties. SOB-maltodextrin microparticles showed higher yield and exhibited lower wettability time, indicating improved encapsulation efficiency and enhanced reconstitution ability. The whey protein isolate-based microparticles exhibited higher solubility (87.65 - 88.62%) and the smallest particle size, reflecting improved emulsification and stabilization properties, whereas soy lecithin-based formulations showed higher absolute surface charge (37.79 - 45.91 mV), lower moisture content, and reduced water activity, indicating superior stability. Spray-dried powders demonstrated good reconstitution properties, making them suitable for food applications. These findings highlight the potential of spray-drying, along with the choice of wall material, as key factors in the effective encapsulation of SOB, paving the way for the development of more stable, functional, and sustainable food products.